Kedudukan Ijtihad dan Fatwa Para Ulama dari Legal Opinion ke Legal Binding - Madnur, Madnur; Sofyan, Aa; Adam, Syahrul; Nahrowi, Nahrowi (Universitas Islam Negeri Raden Intan Lampung, 2023)
The role of ijtihad and fatwa in Indonesia has undergone a transformation over time. This transformation is reflected in the adoption of several binding regulations (legal binding) based on the results of ijtihad and fatwas issued by competent authority institutions. This process reflects the evolution of the role of ijtihad and fatwa in forming the legal basis that applies, provides direction, and binds Indonesian society. This research is qualitative research with a normative legal approach accompanied by a literature review. The data analysis used is content analysis. The research findings show that the process of legalizing ijtihad and fatwa as binding rules is one option in responding to problems. However, not all of these efforts are able to provide comprehensive solutions to every problem, and sometimes they can even give rise to new debates and problems amidst the diversity of Indonesian society.